HEGEMONIC MASCULINITY AND GENDER PERFORMATIVITY OF AN ANDROGYNOUS MALE MODEL IN SURABAYA - Dwi N. C. Sri Kusumaningtyas; Silvy Chintia Adelia; Ephrilia Noor Fitriana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article aims to analyze the emergence of hegemonic masculinity shown by the androgynous model in Surabaya. This study applies gender performativity by Judith Butler to elaborate on how hegemonic masculinity is manifested. The result of this study reveals that the emergence of hegemonic masculinity is negotiated. Since the idea of androgyny is stigmatized and marginalized, the embodiment of the male androgynous model carries a new standard of masculinity and holds legitimation in society. Nevertheless, He still needed to perform the idea of heteronormativity, for example throughout his sexual orientation, personality and daily outifits. As a result, this narrative infers that in the practice of hegemonic masculinity, the male androgynous still needs to strive to earn legitimation by adopting the concept of gender performativity.